Prevalence, risk factors and clinical features of sensory A-V pattern exotropia - Zhu, Bin-Bin; Wang, Xiang-Jun; Fu, Li-Cheng; Yan, Jian-Hua (International journal of ophthalmology, 2025)
AIM: To investigate the potential mechanisms of A-V pattern and evaluate the surgical outcomes used in the treatment of sensory exotropia. METHODS: The medical records of patients with sensory A-V pattern exotropia who underwent strabismus surgery between May 2014 to June 2019 was retrospectively reviewed. The control group included sensory exotropia patients without A-V pattern and concomitant A-V pattern exotropia patients with normal vision who undergone strabismus surgery over this same time period. Ocular alignment, best corrected visual acuity, oblique muscle function, and stereopsis records were collected. RESULTS: Among the 843 eligible patients, 91 (10.79%; 39 males and 52 females) had A-pattern (54, 6.4%) or V-pattern (37, 4.4%). Age at onset of vision impairment was 4±5y and at the time of surgery was 25±9y. Statistically significant negative correlations were present between impaired visual acuity and the pre-operative exodeviation (r=-0.198, P=0.016) and patterns (r=-0.207, P=0.015). Age at surgery and exodeviation in patients with concomitant A-V pattern exotropia was significantly earlier as compared with that of sensory A-V pattern exotropia and sensory exotropia (both P<0.0001). There were no significant differences in these clinical variables between sensory exotropia with or without A-V pattern. Deviation and pattern were significantly reduced in patients receiving horizontal rectus surgery with or without oblique muscle surgery (both P<0.0001). CONCLUSION: The prevalence of sensory A-V pattern exotropia in our study is 10.79%. Visual acuity represents an important factor contributing to the occurrence and development of A-V pattern. Isolated horizontal rectus surgery can provide a good option for the correction of sensory A-V pattern exotropia.